PENGARUH INTRAPRENEURSHIP TERHADAP KINERJA PERUSAHAAN MANUFAKTUR DI TANGERANG - Rita Friana; Ina Indriana (Jurnal Manajemen., 2015)
This study aims to investigate the influence of intrapreneurship on theperformance of manufacturing companies in Tangerang. The population was managerof a manufacturing company in the province of Banten. This study developed andtested a theoretical model where the variable intrapreneurship shaped by factors ofinnovation, risk / uncertainty, risks / challenges, competitive energy, proactive andautonomy, and performance on financial performance variables, variables and variableproductivity growth and repair. Based on the questionnaire, which is selected usingpurposive sampling method of data obtained from a sample of 25 medium-sizedcompanies manufacturing in Tangerang. This study uses confirmatory analysis basedon structural equation modeling (SEM). This research model using AMOS 21.0. Theresults of this study revealed that intrapreneurship has a multidimensional structure.Innovation factors, risks / challenges, competitive and proactive energy can explainwell intrapreneurship. This model proved its effect on the growth and repair.Intrapreneurship affect the growth and repair. This study contributes to theoryhighlights the importance of intrapreneurship-forming factors and their effects in themodel. This is helpful for researchers looking for appropriate performance measuresand intrapreneurs aims to support their decisions and evaluate their performance.